PENGARUH PERTUMBUHAN ASET TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Perusahaan Sektor Pertambangan yang terdaftar Di Bursa Efek Indonesia Periode 2007 - 2016) - Wiwin Triyani; Bambang Mahmudi; Abdul Rosyid (Tirtayasa Ekonomika, 2018)
This study aims to determine the effect of asset growth on company value with probability as intervening variable. The population in this study is mining sector companies listed in IDX period 2007-2016. The sample of research is 11 companies samples by using purposive sampling method. Analytical methods used were outlier test, classical assumption test, partial test (t test), and path analysis.The result of hypothesis test and path analysis shows that: 1) asset growth has an effect on probabiltity, 2) asset growth and probability have no effect to company value, 3) probability able to mediate relationship of asset growth to company value.Keywords: Asset Growth, Probability, Company Value.